2006
DOI: 10.1002/ajmg.c.30082
|View full text |Cite
|
Sign up to set email alerts
|

Genetic counseling and ethical issues for autism

Abstract: Exciting progress is being made in the journey toward discovery of genes conferring risk for autism and autism spectrum disorders. Currently, genetic counseling for idiopathic autism rests on clinical diagnosis and empiric risk estimates. While no genetic test for risk of autism currently exists, it is possible that such a test may emerge in the near future, and that commercial availability may precede adequate understanding of test characteristics. The complexity of multifactorial conditions like autism raise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 30 publications
0
43
0
Order By: Relevance
“…Therefore, it is critical that these data are provided to families in a sensitive manner, with extensive counseling that helps them evaluate risk as we understand it at this time. 33 It is important to convey that recurrence estimates are on the basis of group averages, and, in most cases, it is not yet possible to counsel parents regarding individual levels of risk. A thorough genetic work-up is essential as part of the etiologic investigation for all individuals with ASD and may have important implications for risk counseling.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is critical that these data are provided to families in a sensitive manner, with extensive counseling that helps them evaluate risk as we understand it at this time. 33 It is important to convey that recurrence estimates are on the basis of group averages, and, in most cases, it is not yet possible to counsel parents regarding individual levels of risk. A thorough genetic work-up is essential as part of the etiologic investigation for all individuals with ASD and may have important implications for risk counseling.…”
Section: Discussionmentioning
confidence: 99%
“…For now, the existing dichotomy regarding the extent of testing in research versus clinical settings is challenging. 301 Existing data do not support routine application of any particular test battery, nor do they suggest that tests currently under investigation be routinely performed on all children with ASDs at this time.…”
Section: Comprehensive Evaluation (See Step 82a)mentioning
confidence: 99%
“…They also promote varying clinical indications for extensive molecular testing and neuroimaging when the clinical validity of a positive finding is yet unknown in many cases. 301 Some investigators have reported a positive yield when, in fact, the identified abnormality was nonspecific, did not relate to a known autism-related etiology, and did not affect counseling and/or management (eg, delayed myelinization on MRI). 302 Medical symptoms should be evaluated on a case-by-case basis; rather than reflect an etiology, an abnormal test result may indicate that a child with an ASD has a coexisting condition (eg, a gastrointestinal disorder).…”
Section: Comprehensive Evaluation (See Step 82a)mentioning
confidence: 99%
“…The limited clinical validity of genetic testing for autism and the related ethical concerns have recently been delineated by McMahon et al 267 It seems of particular relevance to keep in mind the complex genetics and uncertainty principle as well as the right of the individual and the family not to participate in genetic testing.…”
Section: Implications For Genetic Counsellingmentioning
confidence: 99%